EFEKTIVITAS METODE STORRYTELLING TERHADAP DISIPLIN ANAK USIA DINI - Ramadhani; Ardimen; Silvianetri (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2025)
Discipline is a person's ability to follow rules, regulations, and responsibilities consistently. The problem in this study is the low level of discipline in children, such as impatience in waiting their turn, reluctance to obey rules, and failure to return items to their proper place, prompting special intervention. This study aims to analyze the effectiveness of group guidance services with storytelling techniques in improving discipline in early childhood at Kupitan 1 State Kindergarten. The research method uses a quantitative approach with a Single Subject Research (SSR) design. The subjects were three children in group B2 who were purposively selected because they had low levels of discipline. Data were obtained through a discipline observation instrument and analyzed using visual analysis between baseline and intervention conditions. The results showed a significant increase in children's discipline scores after the intervention. The average score in the baseline phase was 43.5% (low category), increasing to 66.13% (high category) in the intervention phase. These findings indicate that storytelling techniques in group guidance are effective in shaping disciplined behavior in early childhood.